COMPARATIVE ANALYSIS OF PATHFINDING ARTIFICIAL INTELLIGENCE USING DIJKSTRA AND A* ALGORITHMS BASED ON RPG MAKER MV - Riska Nurtantyo Sarbini; Irdam Ahmad; Romie Oktovianus Bura; Luhut Simbolon (Jurnal Riset Informatika, 2022)
In most games, an artificial pathfinding intelligence is required for traversing the fastest discovery. It is essential for many video games, particularly Role Playing Games (RPGs). The algorithm pathfindings implemented in this game are A* and Dijkstra Algorithms. This study aims to test an artificial intelligence system for discovering routes using the A* and Dijkstra algorithms based on RPG Maker MV. The result showed that from the time obtained, in the experiment on eight nodes using the Pathfinding mechanism of A* algorithm has faster result in discovering the nearest route with the time 08:15:23 with format (mm:ss: ms) whereas Dijkstra Algorithm has a 34:47:43 time result. The time record needed represents the distance between the search nodes. It indicates that the multiple weighting in the impassable nodes caused the cost calculation process becomes faster and more efficient.